'The Diamond': a structure for simulation debrief. (June 2015) - Jaye, Peter; Thomas, Libby; Reedy, Gabriel
Summary Background Despite debriefing being found to be the most important element in providing effective learning in simulation‐based medical education reviews, there are only a few examples in the literature to help guide a debriefer. The diamond debriefing method is based on the technique of description, analysis and application, along with aspects of the advocacy‐inquiry approach and of debriefing with good judgement. It is specifically designed to allow an exploration of the non‐technical aspects of a simulated scenario. Context The debrief diamond, a structured visual reminder of the debrief process, was developed through teaching simulation debriefing to hundreds of faculty members over several years. The diamond shape visually represents the idealised process of a debrief: opening out a facilitated discussion about the scenario, before bringing the learning back into sharp focus with specific learning points. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> Debriefing is the most important element in providing effective learning in simulation‐based medical education reviews </boxed-text> Innovation The Diamond is a two‐sided prompt sheet: the first contains the scaffolding, with a series of specifically constructed questions for each phase of the debrief; the second lays out the theory behind the questions and the process. Implication The Diamond encourages a standardised approach to high‐quality debriefing on non‐technical skills. Feedback from learners and from debriefing faculty members has indicated that the Diamond is useful and valuable as a debriefing tool, benefiting both participants and faculty members. It can be used by junior and senior faculty members debriefing in pairs, allowing the junior faculty member to conduct the description phase, while the more experienced faculty member leads the later and more challenging phases. The Diamond gives an easy but pedagogically sound structure to follow and specific prompts to use in the moment.